Tari Dolalak Grup Dewangga sebagai Arena Sosial Budaya: Praktik, Modal, dan Identitas Anak Muda di Purworejo - Febriyanti, Lusiana; Putri, Rimasari Pramesti (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Tari Dolalak Grup Dewangga is a traditional performing art originating from Purworejo that has experienced socio-cultural transformation through the active participation of young people. This study aims to analyze Tari Dolalak Grup Dewangga as a socio-cultural arena by examining artistic practices, forms of capital, and the construction of youth identity. The research employs a qualitative method with a cultural sociology approach to explore the dynamics of tradition, innovation, and social interaction within the performing arts context. The findings indicate that Tari Dolalak Grup Dewangga functions as a socio-cultural arena in which young participants accumulate and negotiate cultural, social, and symbolic capital through dance practices, performance strategies, and community engagement. These processes enable young people to gain recognition, strengthen social networks, and express collective identity rooted in local culture. In conclusion, Tari Dolalak Grup Dewangga plays a significant role in shaping youth identity while simultaneously sustaining and recontextualizing local cultural values in the contemporary era. The findings of this study indicate that the Dewangga Group's Dolalak Dance is not only a space for cultural expression but also a social arena that allows young people to build cultural identities through the accumulation of cultural, social, and symbolic capital. Practically, these research findings have implications for efforts to preserve local culture, particularly in encouraging the involvement of the younger generation as key actors in the revitalization and innovation of traditional arts to ensure their relevance amidst social change